Pendidikan Kesehatan tentang Pemberian Makanan Pendamping ASI pada Ibu yang Mempunyai Bayi 6-24 Bulan - Nurbaiti Nurbaiti; Gustina Gustina (Jurnal Abdimas Kesehatan (JAK), 2021)
Growth in infants and nutritional problems in children are often caused by the inaccuracy of parents in their habits of inappropriate breastfeeding and complementary feeding, and mothers are less aware that babies aged 6 months already need complementary feeding. mothers in good quantity and quality. At the age of 6 months apart from breastmilk, the baby can start to be given complementary foods, because at this age the baby already has a chewing reflex with stronger digestion. In giving baby food, it is necessary to pay attention to the punctuality of delivery, frequency, type, quantity, foodstuff, and method of manufacture, improper infant feeding habits, such as feeding too early or too late, insufficient food given and inadequate frequency. this can have an impact on the health and nutritional status of the baby. Based on the data obtained from the health office, it is known that from 12 districts the prevalence of malnutrition and malnutrition based on the BB / U indicator is 17.2% and based on the TB / U indicator is 20.2%. This community service aims to provide information and improve the skills of mothers in complementary feeding of breast milk. This community service was carried out in the Work Area of the Simpang Kawat Puskesmas, at the time of January 2020 the service method used a survey approach, lectures and discussions. The results obtained by mothers can understand the meaning of complementary foods for breast milk, the benefits of complementary foods for breast milk and the schedule for which they are given.